Effect on effective diffusion coefficients and investigation of shrinkage during osmotic dehydration of apricot - Togrul, Inci Turk; Ispir, Ayse (Pergamon-Elsevier Science Ltd, 2007)
This article represents the results of the variation in density and shrinkage of apricots during its osmotic dehydration. Shrinkage was investigated by means of dimensionless volume, diameter and length. Various osmotic agents such as sucrose, glucose, fructose, maltodextrin and sorbitol were used. It was found that the shrinkage of apricots could be well correlated with the moisture content of the sample during osmotic dehydration. The relationship between dimensionless parameters and moisture content was investigated by using eight non-linear models for each osmotic agent. It was find that the following proposed model can be confidently use for explaining the effect of shrinkage during osmotic dehydration of apricots. V/V-0, D/D-0, L/L-0, rho/rho(0) = a + b .exp(cX) + d . exp(e.X-f) In addition, the osmotic dehydration kinetics of apricots with and without shrinkage was studied. The effective diffusivities calculated from the diffusional model with and without shrinkage varied from 10.342 x 10(-9) m(2)/s to 5.139 x 10(-9) and from 1.755 x 10(-10) and 0.767 x 10(-10) m(2)/s, respectively. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: osmotic dehydration; apricot; shrinkage; mass transfer